2019
DOI: 10.1088/1361-6587/aaf4ea
|View full text |Cite
|
Sign up to set email alerts
|

SOLPS simulations with electron kinetic effects

Abstract: Power exhaust is one of the critical issues for tokamak edge plasma research. Electron kinetic effects may play an important role in future fusion devices. The KIPP code was coupled to a 1D version of SOLPS with an iterative algorithm [1, 2] to study the kinetic effects in a systematic way. The KIPP-SOLPS coupling algorithm allows us to incorporate kinetic electrons into the already sophisticated fluid model (B2) self-consistently. The KIPP-SOLPS coupling simulation results with pure deuterium and with carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Non‐Maxwellian effects of electron distribution functions on the effective ionization rate coefficient S cr in self‐consistent KIPP‐SOLPS coupling simulations were investigated in ref. , where the cut‐off level max = 10 was found to provide good agreement between the rate coefficient S cr calculated from Equation (18) with Maxwellian electron distribution function f M and that taken from the ADAS database, as shown in Figure . The comparison between line radiation coefficient false∑k,jj>kΔEjkAitalickjαj calculated with max = 10 and f M and that from the ADAS database is also shown in Figure .…”
Section: Numerical Validation Of the Inelastic Operatormentioning
confidence: 57%
See 4 more Smart Citations
“…Non‐Maxwellian effects of electron distribution functions on the effective ionization rate coefficient S cr in self‐consistent KIPP‐SOLPS coupling simulations were investigated in ref. , where the cut‐off level max = 10 was found to provide good agreement between the rate coefficient S cr calculated from Equation (18) with Maxwellian electron distribution function f M and that taken from the ADAS database, as shown in Figure . The comparison between line radiation coefficient false∑k,jj>kΔEjkAitalickjαj calculated with max = 10 and f M and that from the ADAS database is also shown in Figure .…”
Section: Numerical Validation Of the Inelastic Operatormentioning
confidence: 57%
“…The first was elucidated in ref. , which showed that non‐Maxwellian tails had little influence on rates. This work is mainly focused on the second effect, which requires the inelastic collision operator in the kinetic code KIPP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations